# Solve the following logarithmic equation: `log_2(3x-2) - log_2 (x-5) = 4`

### 2 Answers | Add Yours

Notice that bases of logarithms are alike, hence, you need to transform the difference into a quotient such that:

`log_2((3x-2)/(x-5)) = 4 =gt ((3x-2)/(x-5)) = 2^4` `3x - 2 = 16(x-5)`

Opening the brackets yields:

3x - 2 = 16x - 80 => -13x = -78 => x = 6

**Hence the solution to the equation is x = 6.**

The equation to be solved is `log_2 (3x - 2) - log_2 (x - 5) = 4`

Use the property of logarithm log a - log b = log(a/b)

`log_2 (3x - 2) - log_2 (x - 5) = 4`

=> `log_2 ((3x - 2)/(x - 5)) = 4`

=> `(3x - 2)/(x - 5) = 2^4`

=> `(3x - 2)/(x - 5) = 16`

=> 3x - 2 = 16x - 80

=> 13x = 78

=> x = 6

**The solution of the equation is x = 6**